Analisis Strategi Pembelajaran Sains Berbasis Salingtemas dalam Membangun Sikap Ilmiah Siswa: sebuah Tinjauan Literatur Sistematis - Sulthon (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The advancement of science will boost technology, technological advancement will bring negative and positive impacts in life, so that students have concern, awareness, scientific attitude and are responsible for their environment, so quality science learning is needed to prevent environmental damage. This study aims to describe science learning with salingtemas to build students' scientific attitudes. The method used in this study is the Systematic Literature Review method, which is a research method to identify, study, evaluate, and interpret data systematically through searching for journal articles from the Google Scholar and Publish or Perish 8 databases published from 2018 to 2024 from the journal search 208 articles were obtained, after being filtered into 34 articles, then selected using the keywords